A Case of a Patient Who Is Diagnosed with Mild Acquired Hemophilia A after Tooth Extraction Died of Acute Subdural Hematoma due to Head Injury - Tomohisa Kitamura; Tsuyoshi Sato; Eiji Ikami; Yosuke Fukushima; Tetsuya Yoda (Case Reports in Dentistry)
Background. Acquired hemophilia A (AHA) is a rare disorder which results from the presence of autoantibodies against blood coagulation factor VIII. The initial diagnosis is based on the detection of an isolated prolongation of the activated partial thromboplastin time (aPTT) with negative personal and family history of bleeding disorder. Definitive diagnosis is the identification of reduced FVIII levels with evidence of FVIII neutralizing activity. Case report. We report a case of a 93-year-old female who was diagnosed as AHA after tooth extraction at her home clinic. Prolongation of aPTT and a reduction in factor VIII activity levels were observed with the presence of factor VIII inhibitor. AHA condition is mild. However, acute subdural hematoma of this patient occurred due to an unexpected accident in our hospital. Hematoma was gradually increased and the patient died 13 days after admission. Discussion. Although AHA is mild, intracranial bleeding is a life-threatening condition. We also should pay attention to the presence of AHA patients when we extract teeth.